2006
DOI: 10.1111/j.1600-0714.2006.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathology of odontogenic tumors

Abstract: Odontogenic tumors are lesions derived from the elements of the tooth-forming apparatus and are found exclusively within the jawbones. This review represents a contemporary outline of our current understanding of the molecular and genetic alterations associated with the development and progression of odontogenic tumors, including oncogenes, tumor-suppressor genes, oncoviruses, growth factors, telomerase, cell cycle regulators, apoptosis-related factors, regulators of tooth development, hard tissue-related prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 179 publications
0
65
0
11
Order By: Relevance
“…[22] Rb Kumamoto et al, (2006) demonstrated increased expression of retinoblastoma (Rb) and phosphorylated Rb in AB than in tooth germs which might have a role in cell proliferation and diff erentiation of odontogenic epithelium. However, another study by Lim and Ahn et al, (2006) using DNA microarray and reverse polymerase chain reaction (more sensitive compared to IHC) revealed downregulation of Rb1 in AB in comparison with dentigerous cyst.…”
Section: Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] Rb Kumamoto et al, (2006) demonstrated increased expression of retinoblastoma (Rb) and phosphorylated Rb in AB than in tooth germs which might have a role in cell proliferation and diff erentiation of odontogenic epithelium. However, another study by Lim and Ahn et al, (2006) using DNA microarray and reverse polymerase chain reaction (more sensitive compared to IHC) revealed downregulation of Rb1 in AB in comparison with dentigerous cyst.…”
Section: Growth Factorsmentioning
confidence: 99%
“…Further studies are needed to confi rm their role. [19] Platelet-derived growth factor (PDGF) AA isoform and its receptor PDGF-α receptor levels were more in malignant ameloblastic tumors when compared to non-metastasizing AB. PDGF ligand and receptor system might participate in malignant transformation of odontogenic epithelium.…”
Section: Growth Factorsmentioning
confidence: 99%
“…Its overexpression was seen in ameloblastoma which suggest that these oncogenes play a role in the pathogenesis of OT through impairment of cell proliferation. [2] Tumor suppressor gene P53 gene also known as TP53 gene has been describes as "the guardian of the genome" is the key gene altered in tumors. It plays a role genomic destruction by persuading apoptosis or arresting the cell cycle.…”
Section: Oncogenesmentioning
confidence: 99%
“…Abundant oncogenes have been recognized, and their genetic material function as growth factors, growth factor receptors, serine/threonine kinases (Mos), nonreceptor tyrosine kinases (Src, Abl), transcription factors (Myc, Fos), and signal transducers (Ras) which contribute in cellular functions related to propagation and differentiation. [2] Activated ras oncogene is the acutely transforming component of Harvey sarcoma virus 15. There are three cellular homologs: K-ras, H-ras, and N-ras.…”
Section: Oncogenesmentioning
confidence: 99%
See 1 more Smart Citation